(untitled) (International Journal of Environmental Sciences, 2025)
Given the undeniable reality that women constitute 50% of the global population and possess significant capabilities to make valuable contributions to a nation’s advancement, it is imperative to place a high level of importance on the empowerment of women as a fundamental aspect of socioeconomic development. The main purpose of this article is to conduct an in-depth examination of the levels of empowerment experienced by women who are employed and those who are not, with a particular emphasis on the unique circumstances found in Bangalore. The current study exhibits a descriptive orientation. The primary data was obtained from a sample of women who have been actively employed in small industries for a duration of five years. Additionally, the study also included a group of women who have not been engaged in small industries during the same time frame. A sample size of 100 respondents has been acquired for each group, employing the Cochran Formula to accommodate an undisclosed population. By employing a rigorous methodology, we have successfully achieved a confidence level of 95% and a margin of error of 10% in our research outcomes. The Questionnaire has been thoughtfully designed, taking into consideration the variables that were identified during the extensive research review. The questionnaire employs Likert scale items to gather data, and we also evaluate its convergent-divergent validity, ensuring that the statistical measures fall within acceptable ranges. The process of accomplishing data analysis involves the presentation of descriptive statistics, which is subsequently followed by hypothesis testing utilizing the SPSS Version 25 and AMOS R Version 23 software tools. The study’s focus is exclusively on the geographical area of Bangalore District, which is situated within the state of Karnataka, India. The focus of our research revolves around the working women and its potential for empowerment, specifically emphasizing small business units. Based on the findings of the study, it is evident that women who are engaged in employment exhibit higher levels of empowerment in various aspects of their lives, including personal, relational, and environmental domains.